2015
DOI: 10.1002/rnj.173
|View full text |Cite
|
Sign up to set email alerts
|

Falls and Use of Assistive Devices in Stroke Patients with Hemiparesis: Association with Balance Ability and Fall Efficacy

Abstract: Preventive measures for individuals using walking aids may be beneficial in reducing the fall rate of community-dwelling stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In contrast to other studies [2,5,19], the fall occurrence in persons who had a stroke reported in this study was lower (31%) and not different from that of the control participants. However, Jalayondeja et al [18] and Kim [45] reported a similar fall incidence in their settings. These studies and the present study were conducted among Asians, and the cultural differences in activities and living environment may contribute to the discrepancy between Western and Asian countries.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast to other studies [2,5,19], the fall occurrence in persons who had a stroke reported in this study was lower (31%) and not different from that of the control participants. However, Jalayondeja et al [18] and Kim [45] reported a similar fall incidence in their settings. These studies and the present study were conducted among Asians, and the cultural differences in activities and living environment may contribute to the discrepancy between Western and Asian countries.…”
Section: Discussionmentioning
confidence: 73%
“…Our finding that use of a walking aid was associated with increased risk of falling after stroke is consistent with previous research. 31 Use of walking aids represents an intervention related to impaired postural control, and as such, it may be a mediator. Nevertheless, use of a walking aid may present a fall hazard if a patient is not clear how to manage the walking aid because of impaired cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The FES was used to assess fall efficacy, the MBI was used to estimate ADLs, and EQ-5D was used to assess QoL. Standardized instruments that are often used in stoke patients were used in all of the measurements in this study 20 , 21 , 22 ) . Our results showed that the OEP significantly improved fall efficacy.…”
Section: Discussionmentioning
confidence: 99%